Correlation between stacking fault energy and lattice parameter in nanocrystalline Fe–Cr–Ni austenitic stainless steels by atomistic simulation study. (2nd October 2017) - Mohammadzadeh, Roghayeh; Mohammadzadeh, Mina
Abstract: The correlation between stacking fault energy (SFE) and lattice parameter of Fe–Cr–Ni austenitic stainless steels was investigated. To obtain this relationship, four Fe–Cr–Ni alloy systems were considered. Molecular dynamics (MD) studies were carried out to calculate the intrinsic stacking fault energy and lattice parameter of Fe–Cr–Ni austenitic stainless steels as a function of composition. The embedded atom method (EAM) inter-atomic potential was used in the MD studies. The results show that as the Cr content increases, the SFE value significantly decreases while lattice parameter increases. Moreover, the results illustrates that the addition of nickel content hardly changes the SFE values, but on the contrary, decreases the lattice parameter. Almost linear dependence of SFE on lattice parameter could be established for Fe–Cr–Ni austenitic stainless steels.